2018
DOI: 10.1117/1.jmi.5.3.035502
|View full text |Cite
|
Sign up to set email alerts
|

Modeling visual search behavior of breast radiologists using a deep convolution neural network

Abstract: Visual search, the process of detecting and identifying objects using eye movements (saccades) and foveal vision, has been studied for identification of root causes of errors in the interpretation of mammograms. The aim of this study is to model visual search behavior of radiologists and their interpretation of mammograms using deep machine learning approaches. Our model is based on a deep convolutional neural network, a biologically inspired multilayer perceptron that simulates the visual cortex and is reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…e results showed that the light scattering imaging results were compared with the pathological results, and the diagnosis coincidence rate was 81.4%, which was consistent with the literature report [17]. At present, deep learning technology has been widely used in various fields, such as military, medicine, and geography [18,19]. Due to the continuous development of imaging technology, a large amount of imaging data has been obtained clinically, but how to mine useful information from the massive imaging data and apply it to the diagnosis of clinical diseases is one of the goals that need to be achieved at present.…”
Section: Discussionsupporting
confidence: 85%
“…e results showed that the light scattering imaging results were compared with the pathological results, and the diagnosis coincidence rate was 81.4%, which was consistent with the literature report [17]. At present, deep learning technology has been widely used in various fields, such as military, medicine, and geography [18,19]. Due to the continuous development of imaging technology, a large amount of imaging data has been obtained clinically, but how to mine useful information from the massive imaging data and apply it to the diagnosis of clinical diseases is one of the goals that need to be achieved at present.…”
Section: Discussionsupporting
confidence: 85%
“…Stember [47] utilized eye tracking with deep learning for generating segmentation masks based on eye tracking data and achieved results that were similar to hand annotations. Similarly, Aresta [48] and Mall [49] utilized gaze information for automatic lung nodule detection and mammogram interpretations. Hermanson [50] conducted a study to identify the visual search patters of dentists while viewing and interpreting periapical dental radiographs.…”
Section: Related Workmentioning
confidence: 99%
“…Mall et al [8] have used mammograms to analyze the proximity of women's breast cancer cells. In the wake of different mammograms gathered from various radiographs, radiology assessments were similarly taken and contributed to CNN's preparation.…”
Section: Introductionmentioning
confidence: 99%